Duration of Tamoxifen Use and the Risk of Contralateral Breast Cancer in BRCA1 and BRCA2 Mutation Carriers - Gronwald, Jacek (2014)
PURPOSE: Women with a mutation in BRCA1 or BRCA2 face a lifetime risk of breast cancer of approximately 80%. Tamoxifen treatment of the first cancer has been associated with a reduction in the risk of a subsequent contralateral cancer. METHODS: We studied 1504 women with a known BRCA1 or BRCA2 mutation, 411 women with bilateral breast cancer (cases) and 1093 women with unilateral breast cancer (controls) in a matched case-control study. Control women were of similar age and had a similar age of diagnosis of first breast cancer as the cases. For each woman who used tamoxifen, the starting and stopping dates were abstracted and the duration of tamoxifen use was calculated. RESULTS: 331 women had used tamoxifen (22%); of these 84 (25%) had completed four or more years of tamoxifen, the remainder stopped prematurely or were current users. For women with up to one year of tamoxifen use, the odds ratio for contralateral breast cancer was 0.37 (95% CI: 0.20 – 0.69; p = 0.001) compared to women with no tamoxifen use. Among women with one to four years of tamoxifen use the odds ratio was 0.53 (95% CI: 0.32-0.87; p = 0.01). Among women with four or more years of tamoxifen use the odds ratio was 0.83 (95% CI: 0.44 -1.55; p = 0.55). CONCLUSION: Short-term use of tamoxifen for chemoprevention in BRCA1 and BRCA2 mutation carriers may be as effective as a conventional five year course of treatment.